Discovering Students’ Social Identities Through Current News Events - Daniela Lucia Alfonso Colmenares (Enletawa Journal)
This qualitative case study explores how the implementation of news report activities reveals aspects of fifth-grade students' social identities in a private school in Tunja, Boyacá. The study involved 44 fifth-grade students, using data collection methods such as student artifacts, participant observations, focus group discussions, and field notes. Five workshops were designed around distinct themes—environmental, sports, entertainment, arts, and political news—to examine social identity through students' connections to their community and environment. Grounded theory analysis revealed that students identify strongly with specific social groups, with behaviors that aim to benefit these groups. A notable finding was the deep connection participants had with animals, perceiving them as extensions of their own self-image. Conversely, students expressed a sense of distance from adults and their decisions, though they recognized adult influence on their development. Additionally, the study highlighted how students have internalized violence as a conflict resolution strategy, despite aspirations toward peace and societal change. These findings suggest that integrating discussions of conflict, identity, and peace in the classroom can encourage students to see themselves as agents of peace and contributors to a more just society.